Modeling the Structure of the Proton: Deeply Virtual Compton Scattering and Generalized Parton Distributions - Poage, Jonathon. (2017)
Abstract: The structure of the proton and its role in Deeply Virtual Compton Scattering (DVCS) are investigated using the spectator model and Generalized Parton Distributions (GPDs). DVCS is a well established means for probing the internal structure of the proton, and GPDs are mathematical objects that are useful for describing the proton's structure with more complexity than Parton Distribution Functions (PDFs). The soft parts of the DVCS amplitudes are evaluated with a partonic interpretation by using the framework of the spectator model, and parametrized models are formed for quark, antiquark, and gluon GPDs. Several parameters for the GPDs are obtained by fitting the GPDs to established PDF parametrizations, as part of an iterative fit procedure. The applications of the GPDs and their contributions to DVCS observables are then explored.; Thesis (Ph.D.)--Tufts University, 2017.; Submitted to the Dept. of Physics.; Advisor: Gary Goldstein.; Committee: Lawrence Ford, Krzysztof Sliwa, Anthony Mann, and Simonetta Liuti.; Keyword: Particle physics.